2002
DOI: 10.1164/ajrccm.165.5.2106074
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Predictors of Wheeze among Farmer Pesticide Applicators in the Agricultural Health Study

Abstract: Pesticides may contribute to respiratory symptoms among farmers. Using the Agricultural Health Study, a large cohort of certified pesticide applicators in Iowa and North Carolina, we explored the association between wheeze and pesticide use in the past year. Self-administered questionnaires contained items on 40 currently used pesticides and pesticide application practices. A total of 20,468 applicators, ranging in age from 16 to 88 years, provided complete information; 19% reported wheezing in the past year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 30 publications
8
170
2
Order By: Relevance
“…The prevalence of adult-onset asthma in our study is similar to that reported for current asthma among California farmers (2.7%) (33) and Norwegian farmers (3.7%) (34). Atopy was defined as a history of doctordiagnosed eczema or hay fever; we (4,35,36) and others (37) have previously used similar questionnaire-based definitions for atopy. We created the two case groups based on responses to three questions (asthma, eczema, and hay fever) in a manner similar to that of Upton and colleagues, who used asthma with and without hay fever to define atopic and nonatopic asthma among adults (37).…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of adult-onset asthma in our study is similar to that reported for current asthma among California farmers (2.7%) (33) and Norwegian farmers (3.7%) (34). Atopy was defined as a history of doctordiagnosed eczema or hay fever; we (4,35,36) and others (37) have previously used similar questionnaire-based definitions for atopy. We created the two case groups based on responses to three questions (asthma, eczema, and hay fever) in a manner similar to that of Upton and colleagues, who used asthma with and without hay fever to define atopic and nonatopic asthma among adults (37).…”
Section: Discussionsupporting
confidence: 85%
“…19,[28][29][30] The AHS cohort consists of licensed pesticide applicators who are responsible for a thorough understanding of pesticide regulations and for the purchase and application of chemicals. 31 Recall of pesticide use by the AHS cohort has been shown to be consistent with the dates these pesticides came onto the market. 31 Comprehensive questionnaire data was used to quantify metolachlor exposure levels, providing discrimination between high and low exposures, rather than defining exposure as Ôever usedÕ metolachlor.…”
Section: Discussionmentioning
confidence: 84%
“…32 Associations between asthma and use of cholinesterase-inhibiting pesticides were observed among Canadian farmers 33 and U.S. pesticide applicators. 34 The strengths of our pooled study are a population-based design, high response rates and detailed information on pesticide use and potential etiologic factors for NHL. The relatively large sample size facilitated the simultaneous evaluation of asthma and pesticide use but was still not enough to carefully evaluate individual pesticides and asthma in relation to NHL.…”
Section: Resultsmentioning
confidence: 99%